PENGUATAN PERAN KELUARGA DALAM KEBERHASILAN ASI EKSKLUSIF MELALUI EDUKASI PIJAT OKSITOSIN - Aulia, Devy Lestari Nurul; Arum Dwi Anjani; Wahida Wahyuni Siahaan; Sharifah Diana (LPPM-Universitas Batam, 2024)
Exclusive breastfeeding coverage according to WHO (2020) is 44%, still less than the 2030 target of 50%. Indonesia’s exclusive breastfeeding in 2021 is 71.58%. Exclusive breastfeeding in the Riau Islands in 2020 reached 44.9%, and in Batam it was 58.1%. This coverage figure is still far from the national target of 80%. Low coverage of exclusive breastfeeding can affect a child's future growth and development. Insufficient milk production and slow release is one of the reasons why mothers do not give exclusive breast milk to their babies. Other factors that influence breast milk production include the mother's nutritional status, Early Breastfeeding Initiation (IMD), family support and the mother's own knowledge. One effort to increase breast milk production is with oxytocin massage. The aims of this activity are 1) Providing education about Exclusive Breastfeeding and how to stimulate breast milk production by doing Oxytocin Massage, 2) Demonstration of Oxytocin Massage for mothers and families to support the success of Exclusive Breastfeeding. This Community Service Activity (PKM) was carried out at PMB